2013
DOI: 10.1111/head.12196
|View full text |Cite
|
Sign up to set email alerts
|

Auriculotemporal Neuralgia Secondary to TMJ Synovial Cyst: A Rare Presentation of a Rare Entity

Abstract: Synovial cysts of the temporomandibular joint are rare, and to our knowledge, only 14 cases have been reported. The most common presentation is local pain and swelling. We present a case of a synovial cyst presenting with neuralgia in the distribution of the auriculotemporal nerve, initially misdiagnosed as trigeminal neuralgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Synovial cysts are true synovial-lined cysts arising from displaced or herniated synovial lining, which may communicate with the joint cavity. Synovial cysts are associated with primary traumatic or inflammatory processes and may be caused by increased intra-articular pressure [1-3].…”
Section: Introductionmentioning
confidence: 99%
“…Synovial cysts are true synovial-lined cysts arising from displaced or herniated synovial lining, which may communicate with the joint cavity. Synovial cysts are associated with primary traumatic or inflammatory processes and may be caused by increased intra-articular pressure [1-3].…”
Section: Introductionmentioning
confidence: 99%
“…On review of the literature, there are 29 reported cases of unilateral synovial cysts of the TMJ in the English literature 1–20. This is the second case report of bilateral TMJ synovial cysts.…”
Section: Discussionmentioning
confidence: 92%
“…The TMJ is a synovial joint with more than 50 cases of (extraneural) cysts reported in the literature. Extraneural cysts in this location can be asymptomatic or symptomatic (causing neural symptoms due to extrinsic nerve compression 3,4,8,23,33 or mastication difficulties because of the mass 2,7,20,32 ). They are derived from the TMJ via non-neural pedicles and can extend in different directions, even intraosseously 2,8,16,26 or intracranially 18,23,33 (Fig.…”
Section: Discussionmentioning
confidence: 99%